Internet Addiction and Its Relationship with Family Functioning in High School Students - Zahra Harsej; Nasrin Mokhtari Lakeh; Farzaneh Sheikholeslami; Ehsan KazemnezhadLeili (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Family-related factors play an important role in adolescent’s addiction to the Internet. Objective: The aim of this study was to examine the relationship between Internet addiction and family functioning in high school students. Materials and Methods: This is an analytical  study with a cross-sectional design conducted on 796 high school students in Rasht city, Iran who were selected using multi-stage cluster random sampling method. Data collection tools were a demographic form, the Young’s Internet Addiction Test, and the Family Assessment Device. Chi-Square test and rank-ordered logistic regression analysis were used for data analysis. Results:The response rate of of students was 86.81%; 85.7% had at least two family members who were using the Internet; 71.2% of students had no addiction, 27.5% were exposed to Internet addiction and 1.3% had Internet addiction. The majority (65.0%) of studnets had unhealthy family functioning. The relationship between Internet addiction and family functioning was statistically significant (P=0,001). There was a significant statistical relationship between Internet addiction and family income (P= 0.003), fatherchr('39')s job (P=0.001), and duartion of internet usage per day (P=0.001). Logistic regression model showed that the family functioning score (OR=1.02, 95% CI;1.01-1.04, P=0.001), duration of Internet usage per day (OR=1.02, 95% CI;1.11-1.20, P=0.0001), and gender (male) (OR=1.02, 95% CI;1.26-2.58, P=0.001) significantly affected Internet addiction. Conclusion:Due to the direct statistical relationship between Internet addiction and family functioning, it is necessary to pay serious attention to the phenomenon of Internet addiction and make appropriate plans for adolescents and their families to use the Internet properly.